Channel width dependence of electrical characteristics of a-Si:H TFTs under bending stresses. (6th March 2017) - Oh, Hyungon; Cho, Kyoungah; Kim, Sangsig
Abstract: In this study, we investigate the electrical characteristics of bendable a-Si:H thin-film transistors (TFTs) with various channel widths as a function of bending stress. Compared with a narrower channel TFT, a wider channel TFT exhibits a stable performance even at a bending strain of 1.3%. Our stress and strain distribution analysis reveals an inverse relationship between the channel width and the channel stress. As the channel width widens from 8 to 50 μ m, the stress experienced by the middle channel region decreases from 545 to 277 MPa. Moreover, a 50 μ m-channel-width TFT operates stably even after a 15 000 bending cycle while the 8 μ m-channel-width TFT fails to operate after a 2000 bending cycle.